(3COH GdcGJHs - (3YHO Gddg Hf eSde Hf bJjHI GdOjnfnhQqj, CHh eMeO, GHf obnJrjnHI, J (B276 (3g` s
(3ChdgG (B:s
(3obnHrjd aUd(B: "(3eYQaI aj GdSeGA hGdfLhe hGdCReGf hGdQjGM(B"(3, Hbhdg(B: (3hGdSajg(B: (3GdLGgd, hGdSag(B: (3GdLgd hGdMSjH ef GdQLGd Ohf GdfSjH s
(3BNQgG (B:s
"(3eG LGA Ydi aYjd(B" (3bGd(B: (3hGdCSeGA GdJj HfjJ Ydi aYjd JLF hCVOGOgG Ydi HfGA hGMO heG Cbd eG JNJda bGdhG cKjQ hbdjd, hcHjQ hUZjQ, hNaja hKbjd, hHWF hSQjY s
(3fSNI SGHYIs
(3hHChdgG JQLeI ddeDda Yf CHf NdcGfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B137s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B16 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdCOHs